Passive Microwave Signatures of Sea Ice Features. - Ketchum,R D , Jr; Lohanick,A W (1977)
An evaluation has been conducted of passive microwave imagery which displayed many different sea ice forms and features of varying age and thickness, and in various stages of formation, deformation, and weathering. The lowest radiometric temperatures. (i.e. brightness temperatures) were displayed by open water, some areas of new ice which presumably had moist surfaces, and some multi-year ice floes and other forms which apparently had experienced considerable internal stress. It has been hypothesized that internal ice structure changes brought about by severe stresses result in a lowered emissivity. The highest radiometric temperatures were displayed by areas of thin ice which presumably no longer had a wet surface, new ice ridges, and frozen melt ponds. The older, thicker areas of first-year ice appeared to have lower radiometric temperatures than the thinner areas of first-year ice. Single multi-year ice floes often display a wide radiometric temperature range. This has been attributed to physical property changes which resulted from summer melting and erosional processes, and from stresses produced by the interaction of floes. The detection of stress fields and/or stress lines through the use of microwave techniques is a new concept developed by evaluation of this data. This concept invites further investigation. (Author)